Measurement of social preference from utility-based choice experiments - Katsunori Yamada; Masayuki Sato; Yasuhiro Nakamoto (Osaka University, Institute of Social and Economic Research (ISER), 2009)
Ever since the classical works of Smith and Veblen, economists have recognized that individuals care about their relative positions and status in addition to their own consumption. This paper addresses a new framework of choice experiments in order to specify the shape of utility function with preference externalities. Theoretical studies on social preference, which are conducted without estimating or calibrating important parameters of social preference and put forward various propositions in accordance with the parameters assumed, can refer to the parameters estimated in this paper. Our findings complement those of happiness studies which support the view of social preference. We show that preference externality is, on average, characterized by jealousy among Japanese respondents, and also that heterogeneity in social preference parameters is driven by differences in income levels, age, and gender.
Keywords: C25; D03; D62; 330; Social preference; Relative utility; Stated preferences; Choice experiment; Nutzenfunktion; Externer Effekt; Soziale Wohlfahrtsfunktion; Schätzung; Japan